Effect of normalization method on classification of speech dysfluencies using LPC, LPCC and WLPCC - Lim, Sin Chee; Sazali, Yaacob, Prof. Madya Dr.; Muthusamy, Hariharan (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.